Multiple resonant controllers strategy to achieve fault ride-through and high performance output voltage in UPS applications - Carballo, Roberto Esteban (2018)
A control strategy to achieve fault ride-through capability and to provide high performance of the output voltage of a single-phase uninterruptible power supply (UPS) inverter is proposed in this study. This strategy consists in controlling the voltage and current waveforms measured at the inverter output filter, with an inner current control loop and an outer voltage control loop, using a plug-in structure based on multiple resonant stages in addition with proportional controllers. In order to achieve stability from no load to short-circuit conditions, the implementation of the multiple resonant controllers includes a compensation of the system phase lag. Moreover, it presents a comparative analysis between two controller structures, the proposed plug-in and the classical proportional + resonant. From this analysis, it can be concluded that the plug-in structure presents improved characteristics of closed-loop output impedance and output voltage dynamic response during fault ride-through events. A controller design methodology to achieve robustness to parametric uncertainties and UPS standard compliance, is detailed. Experimental results from a single-phase 2 kVA inverter prototype are presented to validate the feasibility of the proposal.